Technical Accuracy of Printed Surgical Templates for Guided Implant Surgery with the coDiagnostiXTM Software. (11th September 2013) - Kühl, Sebastian; Payer, Michael; Zitzmann, Nicola Ursula; Lambrecht, Jörg Thomas; Filippi, Andreas
Abstract: Background: Printing of templates for guided surgery represents an alternative to laboratory manufactured templates. Purpose: To determine the technical accuracy of a virtually designed and printed surgical template for guided implant surgery based on a surface scan of a cast model using the coDiagnostiX TM software. Materials and Methods: Cast models and the virtual planning data of nine patients receiving guided implant surgery with the coDiagnostiX software were analyzed. The original cast models were equipped with three titanium pins and scanned with a three‐dimensional scanner. The scans were uploaded in the coDiagnostiX software and the virtual surgical templates were designed including the sleeves at their original positions. After printing the surgical templates, the sleeve positions were determined by optical scanning, and deviations were calculated and compared with the virtual positions of the sleeves. Results: The sleeves showed a mean three‐dimensional deviation of 0.22 mm (range: 0.07–0.38 mm) in the center of the sleeve top, 0.24 mm (range: 0.08–0.36 mm) in the center of the sleeve bases and a mean angular deviation of 1.5° (range: 0.4°–3.3°) compared with the virtual positions. Conclusions: A high accuracy can be achieved using printed templates for guided implant surgery, by taking into account all sources of inaccuracies.